MOTIVASI DAN KINERJA ANGGOTA DALAM ORGANISASI - Ambia B Boestam (Jurnal Ilmu dan Budaya, 2018)
The significant contribution of motivation to work performance has been unquestioned. When good performance of members of the community in an organization is achieved, the goals of a given organization can be attained with less costs. Of the three elements making up motivation, efforts are as important as needs and the organization’s objectives: efforts should be in concordance with the organization’s objectives. The paper is an attempt to make the analysis of motivation and attainment of the organizations’ objectives. Relevant theries of motivation are used and method used is qualitative research method. The analysis has confirmed the positivecorrelation between motivation and work performance, and that other factors share the influence include leadership, merit system, group work, and work atmosphere